2018
DOI: 10.3892/or.2018.6721
|View full text |Cite|
|
Sign up to set email alerts
|

Long intergenic non‑protein coding RNA 152 promotes multiple myeloma progression by negatively regulating microRNA‑497

Abstract: Long intergenic non-protein coding RNA 152 (LINC00152, also known as cytoskeleton regulator RNA) is reportedly involved in the development and progression of various types of human malignancy. However, the functional role of LINC00152 in multiple myeloma (MM) and the underlying molecular mechanisms have remained elusive. The present study aimed to investigate the role of LINC00152 in the genesis of MM and the potential molecular mechanisms. It was identified that the expression of LINC00152 was significantly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Growing evidence has suggested that a number of lncRNAs contribute to the progression of MM, and can serve as effective diagnosis markers, and therapeutic targets for MM [9,10]. Yu et al [26] reported that long intergenic non-protein coding RNA 152 drove MM progression by negatively regulating miR-497. Shen et al [27] revealed that lncRNA MEG3 promoted MM progression by functioning as a ceRNA to regulate HOXA11 expression by sponging miR-181a.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has suggested that a number of lncRNAs contribute to the progression of MM, and can serve as effective diagnosis markers, and therapeutic targets for MM [9,10]. Yu et al [26] reported that long intergenic non-protein coding RNA 152 drove MM progression by negatively regulating miR-497. Shen et al [27] revealed that lncRNA MEG3 promoted MM progression by functioning as a ceRNA to regulate HOXA11 expression by sponging miR-181a.…”
Section: Discussionmentioning
confidence: 99%
“…In thyroid cancer, LINC00152 acts as a miR-497 'sponge', downregulating its downstream target, brain-derived neurotrophic factor (BDNF), to promote the proliferation and invasion of papillary thyroid cancer cells (71). In multiple myeloma, LINC00152 acts as an oncogene and regulates cell growth by targeting miR-497 expression (72).…”
Section: Epigeneticsmentioning
confidence: 99%
“…A recent publication also found LINC00152 to regulate proliferation and apoptosis in multiple myeloma, confirming our findings. In this publication, Tianhua et al claim that LINC00152 acts as a sponge, hence a negative regulator of miR497 [17].…”
Section: Positive Regulatory Feedback Between Stat3 and Stair18mentioning
confidence: 99%